Development of scanning technique for sTGC detectors production quality control. Issue 1 (January 2016) - Teterin, P E; Filippov, K A; Konovalov, S P; Mikenberg, G; Romaniouk, A; Shchukin, D; Shoa, M; Smakhtin, V; Smirnov, S Yu; Sosnovtsev, V V; Tikhomirov, V O; Tsekhosh, V I; et al.
Abstract: The innermost station of the ATLAS muon end-cap system will be replaced during the forthcoming Phase-I upgrade of the ATLAS detector. The small-strip Thin Gap Chambers (sTGC) are supposed to operate at harsh radiation conditions of super LHC. X-ray scanning technique for production quality control is proposed to ensure long-term reliability of these chambers. It allows to reveal different types of technological defects critical for sTGC chambers operation.